2014
DOI: 10.9790/0853-13564953
|View full text |Cite
|
Sign up to set email alerts
|

Students Perception towards Problem Based Learning

Abstract: The purpose of this study was to determine student perceptions of the methods used to teach pharmacology via problem-based learning (PBL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
3
7
1
2
Order By: Relevance
“…All of the students agreed that learning of facts, diagnostic, and therapeutic skills was significantly enhanced by CBL sessions. 18 A study done in medical school in Mexico also confirms our findings that students had an acceptable level of agreement in having carried out activities related to elaboration of knowledge, such as analyzing and answering questions, formulating hypothesis, and understanding the application of pharmacological knowledge. 21 A study by Chilwant 15 reported that 73% of students were motivated for self-study and 71% of students think that their performance in university examination will be better.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…All of the students agreed that learning of facts, diagnostic, and therapeutic skills was significantly enhanced by CBL sessions. 18 A study done in medical school in Mexico also confirms our findings that students had an acceptable level of agreement in having carried out activities related to elaboration of knowledge, such as analyzing and answering questions, formulating hypothesis, and understanding the application of pharmacological knowledge. 21 A study by Chilwant 15 reported that 73% of students were motivated for self-study and 71% of students think that their performance in university examination will be better.…”
Section: Discussionsupporting
confidence: 80%
“…Our faculty admitted that the whole experience was very motivating and it has improved their knowledge about newer TL methods. The faculty feedback was positive and so wanted to incorporate CBL for other important topics and combine it with traditional lectures methods, which are similar to the findings concluded by Dube et al 18 Student attendance has been recognized as a reliable parameter measuring student satisfaction with the learning process. 22 The significant increase in attendance of students in CBL classes is similar to the CBL study reported by Klegeris and Hurren 22 and Smith and Cook.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, students in PBL often report greater satisfaction with their experiences than non-PBL students 23. On the other hand, some of the students in other study reported a negative perception toward PBL and the reason was that some students dominate while others are passive in the PBL discussion 24. In regard to the students’ perception toward the PBL sessions benefits, our study revealed that PBL was a helpful tool for most of the students to increase their knowledge of basic science.…”
Section: Discussionmentioning
confidence: 70%
“…A similar finding reported that participants feel that PBL is too time consuming. [93237] The time consumption in PBL might be due to long literature searches, posting the literature search in the discussion board, and finally preparing the presentations. In summary, our result showed that a majority of the students positively responded to the statements assessing the benefits of PBL.…”
Section: Discussionmentioning
confidence: 99%